PERAN UNI AFRIKA DALAM MENANGANI KELOMPOK MILITAN BOKO HARAM DI NIGERIA - Levina Chairunnisa; Idjang Tjarsono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research will unravel the conflict in Nigeria due to terrorist attacks by a movement called Boko Haram. The author then attempts to present an analysis of the factors behind the actions of the Boko Haram. In spesific, this research will unravel how African Union as international organization who responsibility to African’s security and peace to handle Boko Haram at Nigeria since 2014-2015. To get a deep comprehension about how African Union worked at Nigeria since 2014-2015, this research used some theory to explain how the result. The theoretical framework applied in this reseacrh are international organization and human security, as well as in international relation science.. This research used nation-state analysis level. The African Union effort at Nigeria include military, economic and humanism. In this situation, African Union do some cooperation with others country and other international organization. When African Union did this mission, they find some problem and obstacle, like the funding and logistic insufficiently, unavailable the diplomacy way with militant groups and the inability of Nigeria to take establish the stability of the country, so that why the conflict is still ongoing.Keywords : African Union, Boko Haram, Nigeria, Terrorism